Agentes indígenas de saúde e educador popular na aldeia Alto do Tambá em Baía da Traição - PB - Silva, Antonio Carlos Souza da (2024)
The work of the Indigenous Health Agent requires un understanding of health practices indigenous culture and from a dialogical and intercultural perspective, so as not to reproduce colonizing models about indigenous peoples. And precisely because of this contextualization of education in the development of this profession, I became interested in Popular Education, considering the direct relationship between popular health knowledge and practices and the social reality of the Potiguara indigenous community in Paraiba in the Alto do Tambá village, in which dialogue is linked to the educational concept in favor of transforming the individual's reality. Popular education with indigenous collectives must take into account the secular culture with which beliefs, habits, customs and traditional knowledge seek to preserve indigenous life in a permanent relationship with the territory and the environment, conflicting with the knowledge and health practices of colonizing peoples. A model of health intervention with indigenous communities requires a review of the assimilation’s practices that are imposed on popular knowledge, without considering the community's health history, knowledge and practices. A popular perspective on collective health, in turn, presupposes an intercultural dialog around indigenous health, promoting dialog and joint commitments to preserving life. The Indigenous Health Agents have their duties well defined when they take up their post, but they need to be aware of their surroundings, of what the community sees as its needs, so that they can focus on disease prevention and health promotion for the indigenous population. Thus, our general objective is to analyze the principles of Popular Education that may be present in the communication process and methodology of action of the Indigenous Health Agents of the Alto do Tambá Village, in Baía da Traição -PB, with the community they serve. The data collection instruments used is: participant observation, photographic record, semi-structured interview and socio-economic profile form. The method of analysis used adopts a qualitative approach, of the case study type, as this is a unique reality, since there is an approximation of the Indigenous Health Agents, as well as the community they serve. With this, we seek to show how the practice of the Indigenous Health Agent expresses an action in popular education. After traveling this path, we were able to conclude that Popular Education is a political approach that values people's participation, the exchange of knowledge, dialogue and awareness as tools for empowerment and social transformation. Thus, it is possible to affirm that there are principles of popular education in the process and methodology of the action of the Indigenous Health Agents of the Alto do Tambá village, such as dialogue, autonomy, lovingness, respect for popular knowledge, stimulating awareness and popular mobilization, empowering this people in the fight for their rights.